2007
DOI: 10.1007/s11669-007-9086-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Description of $${\hbox{SrO-Al}_{2}\hbox{O}_{3}}$$ System and Comparison with Similar Systems

Abstract: The Al 2 O 3 -SrO binary system has been studied using the CALPHAD technique in this paper. The modeling of Al 2 O 3 in the liquid phase is modified from the traditional formula with the liquid phase represented by the ionic two-sublattice model as (Al 3+ , Sr 2+ ) P ( AlO 1À 2 , O 2-) Q . Based on the measured phase equilibrium data and experimental thermodynamic properties, a set of thermodynamic functions has been optimized using an interactive computer-assisted analysis. The calculated results are compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 23 publications
5
33
0
Order By: Relevance
“…20 In practice, Sr 12 Al 14 O 32 Cl 2 decomposes at temperatures below the eutectic melting point of SrAl 2 O 4 and Sr 3 Al 2 O 6 (1560°C). 16 The Sr 12 Al 14 O 32 Cl 2 phases obtained in the present study were found to almost fully (e.g., 93% in Table I decreases in the amounts of SrCl 2 , confirming the evaporation of SrCl 2 , which preferentially occurred at >1300°C. The starting compositions examined in the present study are also plotted in Fig.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…20 In practice, Sr 12 Al 14 O 32 Cl 2 decomposes at temperatures below the eutectic melting point of SrAl 2 O 4 and Sr 3 Al 2 O 6 (1560°C). 16 The Sr 12 Al 14 O 32 Cl 2 phases obtained in the present study were found to almost fully (e.g., 93% in Table I decreases in the amounts of SrCl 2 , confirming the evaporation of SrCl 2 , which preferentially occurred at >1300°C. The starting compositions examined in the present study are also plotted in Fig.…”
Section: Discussionsupporting
confidence: 72%
“…The residue is shared between Sr 3 Al 2 O 6 and SrAl 2 O 4 phases, which are eutectic equilibrium phases in the SrO-Al 2 O 3 pseudo-binary system. 16 Relative densities of samples after sintering at 1200°C and 1300°C for 6 h were 63% and 83%, respectively. They still have an open-pore microstructure.…”
Section: (1) Effect Of Sintering Temperaturementioning
confidence: 96%
See 1 more Smart Citation
“…Sr–Al–O:Eu 2+ particles were synthesized using a molar ratio of (Sr, Eu) 7 Al 12 O x . From SrO‐Al 2 O 3 diagrams, it was clear that the SrAl 2 O 4 crystalline phase could be obtained if the composition ratio was changed such that the SrO/Al 2 O 3 ratio was 7:12 . Sr–Al–O phosphors are known to form several intermediate Sr–Al–O phases during synthesis .…”
Section: Resultsmentioning
confidence: 99%
“…This description was further improved by introducing ternary interaction parameters according to the Al 2 O 3 eSrO pseudo binary system modeled by Ye et al [11]. The improved thermodynamic description was used to calculate phase diagrams as shown in Figs.…”
Section: The Alesreo Systemmentioning
confidence: 99%